2017
DOI: 10.3389/fped.2017.00263
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Genomic Information in Pediatric Leukemia

Abstract: Pediatric leukemia remains a significant contributor to childhood lethality rates. However, recent development of new technologies including next-generation sequencing (NGS) has increased our understanding of the biological and genetic underpinnings of leukemia, resulting in novel diagnostic and treatment paradigms. The most prevalent pediatric leukemias include B-cell acute lymphoblastic leukemia (B-ALL) and acute myeloid leukemia (AML). These leukemias are highly heterogeneous, both clinically and geneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…As previously mentioned, the Muscleblind Like Splicing Regulator ( MBNL1 ), Zinc Finger E-Box Binding Homeobox 2 ( ZEB2) , MLL gene, and E74-like factor 1 ( ELF1 ) genes are disproportionately prevalent in pediatric AML tumors in comparison to adult AML tumors [ 9 , 26 ]. Further, mutations in DNA methyltransferase 3 alpha ( DNMT3A ) and tumor protein 53 ( TP53 ) genes, which drive AML in adult patients, are absent in most pediatric AML cases [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, the Muscleblind Like Splicing Regulator ( MBNL1 ), Zinc Finger E-Box Binding Homeobox 2 ( ZEB2) , MLL gene, and E74-like factor 1 ( ELF1 ) genes are disproportionately prevalent in pediatric AML tumors in comparison to adult AML tumors [ 9 , 26 ]. Further, mutations in DNA methyltransferase 3 alpha ( DNMT3A ) and tumor protein 53 ( TP53 ) genes, which drive AML in adult patients, are absent in most pediatric AML cases [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expanded testing for pediatric leukemias and lymphomas at diagnosis may allow for the incorporation of targeted therapies early on, as opposed to high-dose chemotherapies that result in short- and long-term toxicities. Current recommendations, while suggesting the importance of molecular profiling in liquid tumors, do not recommend standard profiling for at least a subset of tumors, unlike in adult patients [ 12 , 13 ]. However, our experience and other studies have demonstrated the feasibility of incorporating sequencing in pediatric cancer care [ 36 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this is the relatively small number of cases investigated. Although this study constitutes one of the biggest cohorts on IgH HTS at diagnosis, the sample size would not have allowed enough statistical power to analyze the association between clonal complexity and EFS or other described prognostic factors of pediatric leukemia, which is indeed a very heterogeneous disease with many prognostic factors present only in small subsets of patients, as, for example, genetic abnormalities ( 52 , 53 ). Furthermore, only patients with IgH recombinations were included in this study and we did not investigate the association between the absence of IgH recombination (which stipulated an exclusion from our cohort) and belonging to a particular group of risk.…”
Section: Discussionmentioning
confidence: 99%
“…NGS has a wide spectrum of applications in laboratory medicine and has become an integrated part of precision medicine. The technology has been widely used in diagnosis, prognosis, and therapy selection for constitutional disorders, oncology, and infectious diseases [3][4][5]. Concurrently, an increasing amount of well curated clinical, genetic, and genomic data is being generated by NGS, further driving the development of precision medicine [6].…”
Section: Introductionmentioning
confidence: 99%